Effect of Packaging Materials on Pigeon pea Seeds Stored under Ambient Conditions - UB MANJUNATHA,; BASAVEGOWDA,; SR DODDAGOUDAR,; IM SANGEETA,; N SUSHILA, (Seed Research, 2026)
The present investigation was conducted to evaluate and identify the suitable packaging materials for storage of pigeon pea cv. TS-3R seeds under ambient conditions. The graded seeds were treated with the combination of fungicide and insecticide (thiram @ 2g/kg + emamectin benzoate 5SG 40 mg/kg of seeds) and packed in seven packaging materials viz.; gunny bag, polylined (700 gauge) gunny bag, HDPE bag with lamination, purdue improved crop storage (PICS) bag, grain pro bag, zero fly bag and trial bag under ambient storage conditions with initial seed moisture content less than 7.9%. The results revealed that treated seeds differed significantly after six months of storage and among the packaging materials the seeds stored in PICS bag recorded higher seed germination (95.17%), seedling vigour index (2211), seedling dry weight (78.92 mg), lowest seed moisture content (7.95%), lower seed infection (1.7%) and electrical conductivity (0.622 dSm-1) which was on par with grain pro bag and Trial bag whereas the lowest was recorded in seeds stored in gunny bag (91.00%, 1891, 76.98 mg, 9.09%, 11.70% and 0.697 dSm-1, respectively). The interaction of seed treatment and packaging material were found to be non-significant throughout the storage period.